2008
DOI: 10.3317/jraas.2008.017
|View full text |Cite
|
Sign up to set email alerts
|

Review: Cardioprotective effects of telmisartan in uncomplicated and complicated hypertension

Abstract: The development of angiotensin II receptor blockers (ARB) as a new class of drugs for the management of hypertension has elicited the attention of many clinicians worldwide with the aim of improving blood pressure (BP) control as well as cardiovascular protection.AmongARB telmisartan has been shown to be characterised by an antihypertensive efficacy fully covering the 24-hour period, thereby allowing to antagonise the adverse effects of early morning BP rise on cardiovascular risk. Other specific effects of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 79 publications
0
13
0
Order By: Relevance
“…Vascular stiffening causes an increase in the amplitude and early return of the reflected wave during systole, with augmentation of the central systolic BP and a resultant increase in AI [18] . Furthermore, the carotid IMT represents structural changes like wall thickening and the formation of atherosclerotic plaques, which are correlated with a greater incidence of atherosclerosis in the coronary circulation and other large arteries [19] . Telmisartan has been shown to cause an insignificant reduction in AI [18] and significant decreases in both BNP [20] and IMT [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Vascular stiffening causes an increase in the amplitude and early return of the reflected wave during systole, with augmentation of the central systolic BP and a resultant increase in AI [18] . Furthermore, the carotid IMT represents structural changes like wall thickening and the formation of atherosclerotic plaques, which are correlated with a greater incidence of atherosclerosis in the coronary circulation and other large arteries [19] . Telmisartan has been shown to cause an insignificant reduction in AI [18] and significant decreases in both BNP [20] and IMT [21] .…”
Section: Discussionmentioning
confidence: 99%
“…Losartan did not inhibit monocrotalineinduced RV hypertrophy (14), while candesartan prevented it (15). Telmisartan, a 5th generation AT1R blocker, is used for the treatment of hypertension and has cardioprotective effects (16). However, little is known about the effects of telmisartan on RV hypertrophy.…”
Section: Introductionmentioning
confidence: 99%
“…In 2002, the LAARS study enrolled 280 hypertensive patients that were randomized to receive losartan (50 mg) or atenolol (50 mg) for 24 months and demonstrated a significant annual IMT decrease of 0.038±0.004 mm in the losartan group (2). Similarly, Tedesco et al demonstrated a significant IMT regression after 24 months of losartan treatment (3).…”
Section: To the Editormentioning
confidence: 99%
“…We believe that telmisartan has different properties for targeting vascular failure. Recently, Grassi et al (2) reported that telmisartan 1) is effective in favoring the regression of cardiac and vascular organ damage, 2) reduces arterial stiffness and improves vascular distensibility and 3) reverses the endothelial dysfunction typical of the hypertensive state, particularly when complicated by chronic kidney disease (CKD) or metabolic syndrome. Telmisartan Randomized Assessment Study in ACE-I Intolerant Patients with Cardiovascular Disease (TRANSCEND) Investigators (3) have reported that telmisartan was well tolerated in patients unable to tolerate angiotensin-converting enzyme (ACE) inhibitors, and that it modestly reduced the risk of the composite outcome of cardiovascular death, myocardial infarction, or stroke.…”
Section: Response To: Telmisartan and Carotid Intimamedia Thickness Rmentioning
confidence: 99%